Prevalence of Non-Communicable Diseases in Adult Members in Selected Wards of Kageshwori Manohara Municipality, Kathmandu, Nepal - Shrestha, Niraj; Shrestha, Binita; Shrestha, Kristina (Nepal Medical College Journal, 2025)
As non communicable diseases (NCDs) have now become a leading cause of morbidity and mortality with its burden rising more in the low income countries like Nepal, community based management of NCDs by mobilizing health workers from basic health service centers may give good results as well as reduce the load for the tertiary centers. For this generating data related to NCD in a particular locality is very important and this is scarce in Nepal which mainly relies on the data provided by the central government. A survey was done in 2 wards of Kageshwori Manohara Municipality of Kathmandu District, Nepal which is undergoing rapid urbanization, in the year 2023 and 2024 AD. This survey which included 2,900 adult participants in which around 1/4th had NCD. The prevalence of hypertension was 13% and diabetes 6.5% with diabetes more prevalent in Brahmin and Chettri caste. These locally generated data along with its use in managing the disease can also be used in raising health awareness in the local settings.